circAFF1 Aggravates Vascular Endothelial Cell Dysfunction Mediated by miR-516b/SAV1/YAP1 Axis - Wang, Hong-guang; Yan, Hua; Wang, Chen; Li, Mi-mi; Lv, Xin-ze; Wu, Hai-dong; Fang, Zhan-hai; Mo, Dong-li; Zhang, Zhi-yuan; Liang, Bin; Lai, Ke-guan; Bao, Jing-yu; et al. (Frontiers in Physiology, 2020)
Pathological vascular endothelial damage caused by hypoxia is the basis of many vascular-related diseases. However, the role of circular RNA in hypoxic vascular injury is still poorly understood. Here we found that hypoxia induced AFF1 circular RNA (circAFF1) can activate the SAV1/YAP1 and lead to the dysfunction of vascular endothelial cells. In HUV-EC-C and HBEC-5i cells, circAFF1 was upregulated under CoCl2 induced hypoxic conditions. The abnormal expression of circAFF1 inhibited the proliferation, tube formation, migration of vascular endothelial cells. The effect of circAFF1 is achieved by the adsorption of miR-516b to release SAV1, which in turn causes the phosphorylation of YAP1. Moreover, we found that the upregulation of circAFF1 in 235 Patients with subarachnoid hemorrhage. Taken together, we clarify the role of circAFF1/miR-516b/SAV1/YAP1 axis in vascular endothelial dysfunction and its potential early diagnostic value of disease caused by hypoxia injury in blood vessels.